Relationship Between Sports Participation After Revision Anterior Cruciate Ligament Reconstruction and 2-Year Patient-Reported Outcome Measures. Issue 9 (July 2019) - ; Bigouette, John P.; Owen, Erin C.; Lantz, Brett (Brick) A.; Hoellrich, Rudolf G.; Huston, Laura J.; Haas, Amanda K.; Allen, Christina R.; Anderson, Allen F.; Cooper, Daniel E.; DeBerardino, Thomas M.; Dunn, Warren R.; et al.
Background: Anterior cruciate ligament (ACL) revision cohorts continually report lower outcome scores on validated knee questionnaires than primary ACL cohorts at similar time points after surgery. It is unclear how these outcomes are associated with physical activity after physician clearance for return to recreational or competitive sports after ACL revision surgery. Hypotheses: Participants who return to either multiple sports or a singular sport after revision ACL surgery will report decreased knee symptoms, increased activity level, and improved knee function as measured by validated patient-reported outcome measures (PROMs) and compared with no sports participation. Multisport participation as compared with singular sport participation will result in similar increased PROMs and activity level. Study Design: Cross-sectional study; Level of evidence, 3. Methods: A total of 1205 patients who underwent revision ACL reconstruction were enrolled by 83 surgeons at 52 clinical sites. At the time of revision, baseline data collected included the following: demographics, surgical characteristics, previous knee treatment and PROMs, the International Knee Documentation Committee (IKDC) questionnaire, Marx activity score, Knee injury and Osteoarthritis Outcome Score (KOOS), and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). A series of multivariate regression models were used to evaluate the association of IKDC, KOOS, WOMAC, and Marx Activity Rating Scale scores at 2 years after revision surgery by sports participation category, controlling for known significant covariates. Results: Two-year follow-up was obtained on 82% (986 of 1205) of the original cohort. Patients who reported not participating in sports after revision surgery had lower median PROMs both at baseline and at 2 years as compared with patients who participated in either a single sport or multiple sports. Significant differences were found in the change of scores among groups on the IKDC ( P < .0001), KOOS-Symptoms ( P = .01), KOOS–Sports and Recreation ( P = .04), and KOOS–Quality of Life ( P < .0001). Patients with no sports participation were 2.0 to 5.7 times more likely than multiple-sport participants to report significantly lower PROMs, depending on the specific outcome measure assessed, and 1.8 to 3.8 times more likely than single-sport participants (except for WOMAC-Stiffness, P = .18), after controlling for known covariates. Conclusion: Participation in either a single sport or multiple sports in the 2 years after ACL revision surgery was found to be significantly associated with higher PROMs across multiple validated self-reported assessment tools. During follow-up appointments, surgeons should continue to expect that patients who report returning to physical activity after surgery will self-report better functional outcomes, regardless of baseline activity levels.